2016
DOI: 10.1080/23294515.2016.1161672
|View full text |Cite
|
Sign up to set email alerts
|

The patient's perspective on the need for informed consent for minimal risk studies: Development of a survey-based measure

Abstract: Background: Recent efforts to study quality improvement (QI) efforts to improve the effectiveness and efficiency of healthcare have raised important questions about ethical boundaries for waiving informed consent. Confusion exists because similar projects can be undertaken for research or QI purposes, a distinction currently used to define Institutional Review Board oversight. However, patients are not aware of such distinctions. We sought to evaluate patients' views of waiving consent for non-invasive project… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 40 publications
(51 reference statements)
2
7
0
Order By: Relevance
“…Various studies have shown that at first glance, participants seem to favor an “ask each time” model in research . Those findings are inconsistent with the results of two studies exploring public attitudes toward consent in biobanking, both indicating that a broad one‐time opt‐in is preferred by the public in general .…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…Various studies have shown that at first glance, participants seem to favor an “ask each time” model in research . Those findings are inconsistent with the results of two studies exploring public attitudes toward consent in biobanking, both indicating that a broad one‐time opt‐in is preferred by the public in general .…”
Section: Resultsmentioning
confidence: 83%
“…Specific individual consent with opt‐in is described by several researchers and ethicists as impractical as it would be too time‐consuming and expensive to ask consent from every patient for every research project . Having participants understand the difference between clinical care and research also takes time .…”
Section: Resultsmentioning
confidence: 99%
“…Transforming the patient encounter into research data also requires accepting changes to privacy and confidentiality, which are important foundations of patient trust and effective health care. Studies demonstrate broad support among patients and consumers for approaches to improving health care that rely on using patient information [7, 8]. They also have consistently found privacy to be a major concern [9–14].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, several studies showed that even if there is good acceptance from the public for research with health data, there is a strong desire of transparency and to be asked for permission before using this information. As illustrated in our scoping review, participants expressed a preference for an "ask me each time" model of consent in research (Flory et al, 2016;Kaplan et al, 2016;Kass et al, 2016;Kelley et al, 2015;Nayak et al, 2015;Sugarman & Califf, 2014;Weinfurt et al, 2016;Whicher et al, 2015). However, the study by Cho et al (2015) noted that when the consent process impacts significantly the feasibility of the research, participants were willing to accept less elaborate approaches.…”
Section: Discussionmentioning
confidence: 99%
“…As the use of de-identified health data is crucial for certain research projects for which consent cannot always be obtained, this result is not very surprising. Several researchers and ethicists described specific individual consent with opt-in as impractical, as it would be too time consuming and expensive to ask consent from every patient for every research project Hoffman & Podgurski, 2012;Kaplan et al, 2016). Few seem to believe that this approach to consent would fit well the needs of LHSs.…”
Section: Discussionmentioning
confidence: 99%